Prevalence and characteristics of spontaneous tinnitus in 11-year-old children. - Humphriss, Rachel; Hall, Amanda J.; Baguley, David M. (International Journal of Audiology, 2016)
Objective: To estimate the prevalence of spontaneous tinnitus in 11-year-old children.Design: A prospective UK population-based study. Study sample: A total of 7092 children from the Avon longitudinal study of parents and children (ALSPAC) who attended the hearing session at age 11 years and answered questions about tinnitus.Results: We estimated the prevalence ofanyspontaneous tinnitus as 28.1% (95% CI 27.1, 29.2%), and the prevalence of ‘clinically significant’ tinnitus as 3.1% (95% CI 2.7, 3.5%). Children were less likely to have clinically significant tinnitus if the tinnitus was ‘soft’ rather than ‘loud’ and if continuous rather than intermittent. Clinical significance was more likely if the tinnitus occurred more than once a week. Neither pitch nor length of history were important determinants of clinical significance. Small increases in mean hearing threshold (of up to 2.3 dB HL) were associated with clinically significant tinnitus.Conclusions: Although the prevalence of any tinnitus in 11-year-old children appears high, the small proportion in which this was found to be clinically significant implies that this does not necessarily indicate a large unmet clinical demand. We would expect approximately one child per class of 30 to have clinically significant tinnitus which is, by definition, problematic.